Effects of anthropogenic factors on the population structure of Pterocarpus angolensis DC in a communal area of Khalavha Village in Vhembe Biosphere - Ndou, Tshihumbudzo (My University, 2024)
Pterocarpus angolensis DC. is an indigenous species of value across Africa. The species have been identified as having a high utilization rate for different purposes. The purpose of the study was to analyze the population structure of P. angolensis, a species in high demand. Ethnobotanical information was collected with an aid of a questionnaire from fifty-three informants. The informants identified two plant parts preferred by the community. The only preferred parts are stem (67%) and bark (33%). The study identified a lack of indigenous knowledge of the species amongst the youth. Some of the uses reported on P. angolensis were firewood (n=33), medicine (n=43), craftwork (n=35), protection (n=16), and timber (n=4). The transect sampling technique was used to document ecological data on the species to analyze its population structure. Fifty-three transects of 100m x 10m were constructed within the population. Ecological parameters recorded included stem diameter, height, and crown health status. Basal stem diameter data recorded on P. angolensis sampling were grouped into seven size classes and displayed an inverse J-shaped curve when analysed. The study showed that the population had more individuals (n=60) within the seedlings size class (0-5cm) when compared to the bigger size classes (20.1-25cm, 25.1-30cm, and >30.1cm). The majority (37%) of P. angolensis individuals had light crown damage which depicts on average an aspect of healthy crowns. Only 1% of sampled individuals had dead crowns. Monitoring of the P. angolensis population will assist in making sure that it stays healthy and viable.
M.Sc. (Botany)
Department of Biological Sciences
Keywords: Pterocarpus anglolensis DC; Anthropogenic factors; UCTD; Population Structure; Khalavha village; Vhembe Biosphere